"They Don't Look at You as a Real Muslim": the racial exclusion of black American Muslim converts. (24th February 2023) - Casey, Patrick Michael
Abstract: There is a growing body of research applying the insights of race theory to the experiences of Muslims in the West, including Muslim converts. Within the U.S. context, much of this research has focused on the experiences of whites, despite the fact that black Americans convert at a much higher rate and make up a considerably larger proportion of the Muslim American population. This study draws attention to the incorporation experiences of black American converts as they work to establish authentic religious identities as legitimate members of a faith community that is comprised mostly of first‐ and second‐generation immigrants. Rather than immigrant incorporation, this study is concerned with the incorporation of an indigenous population into a primarily immigrant one. Findings suggest that many black converts face difficulty being recognized as valued members of their adopted religious communities, and many report experiences of racial prejudice and discrimination.